The emergence of birdwatching in China: history, demographics, activities, motivations, and environmental concerns of Chinese birdwatchers. Issue 3 (2nd July 2018) - WALTHER, BRUNO ANDREAS; WHITE, ARON
Summary: Birdwatching has become a global pastime and a driving force for conservation. Because of China's economic and environmental importance, the emergence of birdwatching as a mass participation leisure activity in China over the past three decades is of global interest. We documented this emergence by conducting an extensive literature search and two online questionnaires which we used to describe the history, geographic distribution, demographics, activities, motivations, and environmental concerns of Chinese birdwatchers. The emergence happened because of (1) the transfer of ornithological knowledge to birdwatchers, (2) the increasing political tolerance to pursue pastimes, (3) the increasing leisure time, affordability of optical equipment, and urbanisation of China's society, (4) increased internet use, and (5) interactions of birdwatchers with the media and foreign birdwatchers. Of the 576 respondents to our questionnaires, two-thirds were male, about half were younger than 35 years of age, approximately 90% were university-educated, and many also had an above-average income and originated mostly from the more urbanised coastal or near-coastal provinces. Our respondents were thus part of China's economic and educational elite who largely birdwatch for enjoyment, but also because of the knowledge gained about the birds' ecology. Many birdwatchers have become concerned about the deteriorating state of the environment and are frustrated about the lack of government action. Within the political constraints set by the government, many birdwatchers support environmental conservation through various activities, which have yielded some conservation successes. However, birdwatching societies remain constrained by the same legislative and administrative restraints which limit the actions of other environmental non-governmental organizations, thus hindering the effective discourse between China's government and its emerging but still strictly controlled and regulated civil society.